Contrasts Within New Zealand Cities: Perceived Liveability Across Five Neighbourhoods in Tāmaki Makaurau Auckland - Besen, Priscila; Burgess, Andrew; Vallis, Stacy; Morrison, Ann; Marks, Stefan; Piri, Imelda; Shafiei, Marzieh (Emerald, 2026)
Purpose: The design and maintenance of neighbourhoods can influence lifestyles, social interactions and quality of life. Tāmaki Makaurau/Auckland’s urban form is marked by extensive urban sprawl and low-density residential-only zones. While a few studies have assessed liveability in selected Aotearoa/New Zealand’s neighbourhoods, studies that compare residents’ perceived liveability across different areas of Auckland remain limited. This study aims to examine urban liveability perceptions in various Auckland neighbourhoods to understand how the built environment and amenities impact residents’ quality of life. Design/methodology/approach: A quantitative research methodology was used, collecting data from 164 residents through an online questionnaire distributed in eight Auckland suburbs. Results from the neighbourhoods of Massey, Mt. Eden, Northcote, Takanini and Saint Heliers are discussed in this paper, comparing areas distributed geographically across the territory which show significant contrasts. The data were analysed using descriptive and inferential (Kruskal–Wallis) statistics and discussed with information from spatial mapping. Findings: Perceptions of liveability vary across neighbourhoods. The overall results show the highest perceived liveability in Mt. Eden and Saint Heliers, and the lowest in Takanini and Massey. Street type, age, disability and work routine also influence perception of liveability. Results align with social deprivation indexes, canopy cover, walking frequencies and proximity to the city centre: higher liveability levels were found in the least deprived and greener areas located closer to the city centre, where there are higher rates of walking. Originality/value: This study highlights the social dimensions of liveability using residents’ perceptions with a holistic approach, including factors such as amenities, infrastructure, transport, safety and sense of community. The findings inform socioeconomic and built environment indicators of liveability, helping to create evidence-based policies and design practices for sustainable and well-connected future neighbourhoods.
Keywords: 44 Human Society; 4406 Human Geography; 33 Built Environment and Design; 3304 Urban and Regional Planning; Basic Behavioral and Social Science; Behavioral and Social Science; 11 Sustainable Cities and Communities; Urban liveability; SDG 11 Sustainable cities and communities; Sustainable urbanisation; Perceived liveability; Social sustainability; Urban design; Urban densification; Urban amenities